Anti-tissue transglutaminase antibodies in inflammatory and degenerative arthropathies - A. Spadaro; M.L. Sorgi; R. Scrivo; A. Picarelli; M. Di Tola; L. Sabbatella; E. Taccari (PAGEPress Publications, 2002)
Recent studies identified tissue transglutaminase (tTG) as the antigen eliciting antiendomysial antibodies (EMA) in celiac disease (CD). Anti-tTG antibodies have therefore been proposed as a serological test for CD. Nevertheless, IgA anti-tTG but not EMA have also been found in inflammatory bowel disease patients, suggesting that these antibodies are linked to a tissue lesion rather than to an auto-immune component of CD. To confirm this hypothesis, we evaluated the presence of IgA anti-tTG in patients with inflammatory and degenerative diseases, in whom tissue lesions presented far away from the intestinal mucosa. The study was carried out on the serum and synovial fluid (SF) of 68 patients with rheumatoid arthritis (RA=33), psoriatic arthritis (PsA=26) and osteoarthritis (OA=9). In RA, PsA and OA sera, IgA anti-tTG were positive in 33%, 42% and 11% of patients, respectively. Serum anti-tTG levels were significantly higher in RA (p<0.0001), PsA (p<0.0001) and OA (p<0.02) with respect to healthy controls. SF anti-tTG levels were significantly higher in PsA (p<0.018) than in OA. A good correlation between serum and synovial fluid anti-tTG levels was found in all arthropathies This study suggests that tTG is not the only antigen of EMA and, furthermore , that IgA anti-tTG antibodies represent a general lesion-associated event. Moreover, the significant correlation between serum and synovial fluid anti-tTG levels allow us to hypothesise that these antibodies could be synthesized in the site of arthritic lesions.